Studies on some fungi in button mushroom cultivated in Akola (Amanatpur) - S, Dandge V (Recent Research in Science and Technology, 2012)
Agaricus bisporus (button mushroom) is an edible Basidiomycetes mushroom native in Europe & North America. It is cultivated in more than 70 countries. It is one of the most commonly widely consumed mushrooms in the world having medicinal value. India produces 20,000 tons of button mushrooms. The reasons for such a low production can be attributed to lack of awareness among masses, shortage of quality spawn, and use of traditional methods of cultivation inadequacy of post harvest disposal facilities. A number of harmful fungi are also encountered in compost & casing soil during the cultivation which causes damage to mushrooms directly or indirectly which can adversely affect the final yield. In present investigation studies on some fungi in Button mushroom cultivated at Akola and some preventive measure were taken into consideration during processing.